2020
DOI: 10.1080/09602011.2020.1760111
|View full text |Cite
|
Sign up to set email alerts
|

Detecting mental health problems after paediatric acquired brain injury: A pilot Rasch analysis of the strengths and difficulties questionnaire

Abstract: and what was found p2Neuropsychological Rehabilitation (c) If relevant, consider translating estimates of relative risk into absolute risk for a meaningful time period Other analyses Report other analyses done-eg analyses of subgroups and interactions, and sensitivity analyses p10-15 Discussion Key results Summarise key results with reference to study objectives p15-20 Limitations Discuss limitations of the study, taking into account sources of potential bias or imprecision. Discuss both direction and magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…For instance, the SDQ items restless-fidgety and liessteals were redundant and needed to be combined. While redundancies between other pairs of items were found, we combined the items restless-fidgety (Percy et al, 2008;Van Roy et al, 2008;Sanne et al, 2009;van de Looij-Jansen et al, 2011;Ortuño-Sierra et al, 2015a,b;Bøe et al, 2016;Lehmann et al, 2017;Garrido et al, 2018;Keller and Langmeyer, 2019;McCarron et al, 2020) and lies-steals (McCarron et al, 2020) as the redundancies have a theoretical base, which is previously documented in the SDQ literature. For example, van de Looij-Jansen et al (2011) showed that the items restless and fidgety form a "minor factor" termed as restlessness within the broader SDQ dimensions of hyperactivity.…”
Section: Comparison Between Factor and Network Modelsmentioning
confidence: 99%
“…For instance, the SDQ items restless-fidgety and liessteals were redundant and needed to be combined. While redundancies between other pairs of items were found, we combined the items restless-fidgety (Percy et al, 2008;Van Roy et al, 2008;Sanne et al, 2009;van de Looij-Jansen et al, 2011;Ortuño-Sierra et al, 2015a,b;Bøe et al, 2016;Lehmann et al, 2017;Garrido et al, 2018;Keller and Langmeyer, 2019;McCarron et al, 2020) and lies-steals (McCarron et al, 2020) as the redundancies have a theoretical base, which is previously documented in the SDQ literature. For example, van de Looij-Jansen et al (2011) showed that the items restless and fidgety form a "minor factor" termed as restlessness within the broader SDQ dimensions of hyperactivity.…”
Section: Comparison Between Factor and Network Modelsmentioning
confidence: 99%
“…For example, the magnitude of the wTO between the item pair restless and fidgety was similar across LSAC Wave 2K (wTO = 0.43), LSAC Wave 3K (wTO = 0.42), LSAC Wave 4B (wTO = 0.42), LSAC Wave 4K (wTO = 0.41), LSAC Wave 5B (wTO = 0.44), and LSAC Wave 6B (wTO = 0.48). The redundancy between items restless and fidgety (Bøe et al, 2016; Garrido et al, 2018; Keller & Langmeyer, 2019; Lehmann et al, 2017; McCarron et al, 2020; Ortuño-Sierra, Chocarro, et al, 2015; Ortuno-Sierra, Fonseca-Pedrero, et al, 2015; Percy et al, 2008; Sanne et al, 2009; van de Looij-Jansen et al, 2011; Van Roy et al, 2008), lies and steals (McCarron et al, 2020), and distractible and persistent (Bøe et al, 2016; Garrido et al, 2018; Hill & Hughes, 2007; Lehmann et al, 2017; McCarron et al, 2020; Ortuño-Sierra, Chocarro, et al, 2015; Ortuno-Sierra, Fonseca-Pedrero, et al, 2015; Sanne et al, 2009) were previously reported across several SDQ versions and were extensively discussed in the SDQ literature.…”
Section: Discussionmentioning
confidence: 90%
“…Table 1 presents the Rasch reliability of the original FH-22 and the short version of the FH-4 Family Health Scale. Based on the data, both versions have good item: Rasch reliability and person Rasch reliability (>0.79 for the original version and >0.80 for the short version) [ 12 ]. The item separation indices of the two versions are not very different, with the short version being slightly higher than the original.…”
Section: Study Resultsmentioning
confidence: 99%
“…However, a limitation of this model is that the social component of family functioning (e.g., family health) has not been sufficiently studied in relation to family members' career-related self-efficacy. Based on the literature review, the following sections provide a critical review of research on family functioning in China, research on occupation-related variables, and research in the SEN family member population [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%